2018
DOI: 10.1111/rda.13157
|View full text |Cite
|
Sign up to set email alerts
|

Blood calcium, glucose and haematology profiles of parturient bitches diagnosed with uterine inertia or obstructive dystocia

Abstract: Bitches with dystocia most often present with clinical signs of uterine inertia (UI). The aetiology of myometrial dysfunction in most of these cases is still not elucidated. We compared blood ionized calcium (iCa) and glucose concentrations in bitches diagnosed with primary UI (PUI, n = 14), secondary UI (SUI, n = 6) or obstructive dystocia (OD, n = 6), and we described their haematology profiles. Bitches diagnosed with UI had a patent birth canal and delivered no puppies yet (PUI) or only part of the whole li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(49 citation statements)
references
References 25 publications
4
40
2
3
Order By: Relevance
“…Currently, our knowledge about the underlying aetiology of canine PUI is still very limited and most studies refer to hormones and metabolic blood parameters, such as progesterone, oxytocin, calcium, and glucose (Bergstrom et al 2010;Bergström et al 2006b;Davidson 2011;Frehner et al 2018;Hollinshead et al 2010;Kraus and Schwab 1990;Lucio et al 2009). PUI is characterized by inadequate/insufficient uterine contractions, and PTGS2 and prostaglandins play an essential role in the coordination of uterine contractions (Challis et al 2002;Noakes et al 2009, Senior et al 1991Senior et al 1993;Senior et al 1992).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, our knowledge about the underlying aetiology of canine PUI is still very limited and most studies refer to hormones and metabolic blood parameters, such as progesterone, oxytocin, calcium, and glucose (Bergstrom et al 2010;Bergström et al 2006b;Davidson 2011;Frehner et al 2018;Hollinshead et al 2010;Kraus and Schwab 1990;Lucio et al 2009). PUI is characterized by inadequate/insufficient uterine contractions, and PTGS2 and prostaglandins play an essential role in the coordination of uterine contractions (Challis et al 2002;Noakes et al 2009, Senior et al 1991Senior et al 1993;Senior et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…All dogs were assigned to one of the respective groups based on history and clinical findings as follows (Frehner et al 2018):…”
Section: Grouping Of Dogsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact aetiology of this condition is unknown, but associations have been made with a lack of circulating oxytocin, elevated progesterone, hypocalcaemia and genetics. 4 In the case of brachycephalic breeds, a large head in relation to a narrow pelvis appears to be the main reason for obstructive dystocia. Recent computed tomography studies of bulldogs showed an overall shorter pelvis and pelvic canal and a narrower pelvic outlet, which are likely to contribute to the high risk of dystocia found in this breed.…”
Section: Diagnostic Imaging: An Essential Tool In the Successful Manamentioning
confidence: 99%
“…The most common reason for dystocia in all breeds appears to be uterine inertia – the failure for the uterus to appropriately contract. The exact aetiology of this condition is unknown, but associations have been made with a lack of circulating oxytocin, elevated progesterone, hypocalcaemia and genetics 4 …”
mentioning
confidence: 99%